Antibody enhances killing of Tritrichomonas foetus by the alternative bovine complement pathway. - Aydintug, M K (1990)
The role of bovine antibody and complement in host defense against Tritrichomonas foetus was measured by using an assay of trichomonad viability based on protozoal uptake of tritiated adenine. Moderate killing was measured in the absence of antibody only with high concentrations of complement-preserved hypogammaglobulinemic bovine serum. However, very low concentrations of hyperimmune serum promoted significant enhancement (P less than 0.05) of killing by complement. Heat inactivation of complement (56 degrees C for 30 min) eliminated antibody-dependent and -independent killing. Similarly, depletion of bovine factor B in serum by heat treatment (50 degrees C for 45 min) abolished antibody-dependent and -independent killing. However, selective inactivation of the classical complement pathway with magnesium ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid did not affect antibody-dependent or -independent killing by complement. These findings demonstrate antibody enhancement of complement-mediated killing of T. foetus by the alternative pathway of bovine complement.